HIPNO-KOMUNIKASI Melakukan Komunikasi Dengan Pendekatan Berbasis Hipnosis - Sudiono, Bambang (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2010)
Communication, not just a word. Its a tool to bring human being to the new world which place more understanding, peace and prosperity. Communication base hypnosis by Neuro-Linguistic Programming, one of tools to open our mind, to reach goal setting and to change mind _set.